2018
DOI: 10.3390/nano8100747
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of NiMn Layered Double Hydroxides for Supercapacitors: A Review

Abstract: The research on supercapacitors has been attractive due to their large power density, fast charge/discharge speed and long lifespan. The electrode materials for supercapacitors are thus intensively investigated to improve the electrochemical performances. Various transition metal layered double hydroxides (LDHs) with a hydrotalcite-like structure have been developed to be promising electrode materials. Earth-abundant metal hydroxides are very suitable electrode materials due to the low cost and high specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 77 publications
0
46
0
Order By: Relevance
“…The intercalated anions are typical carbonates (CO 3 2À ), but can be simplys ubstituted by other anions( e.g.,N O 3À ,S O 4 2À ,C l À , Br À ). NiFe LDH, [65][66][67] NiMn LDH, [17,25] and NiCo LDH, [16,17] have been studied for OER, but main problem associated with Ni-based LDHs is their low conductivity (Ni 3 Fe LDH:1 .943 Scm; Ni 3 Fe LDHÀNH 3 :3 .759 Scm; Ni 3 Fe LDHÀAr:3 .061 Scm), which is ag eneral dilemma with hydroxides. NiFe LDH, [65][66][67] NiMn LDH, [17,25] and NiCo LDH, [16,17] have been studied for OER, but main problem associated with Ni-based LDHs is their low conductivity (Ni 3 Fe LDH:1 .943 Scm; Ni 3 Fe LDHÀNH 3 :3 .759 Scm; Ni 3 Fe LDHÀAr:3 .061 Scm), which is ag eneral dilemma with hydroxides.…”
Section: Ni-based Layered Double Hydroxide Nanosheet Oer Electrocatalmentioning
confidence: 99%
See 3 more Smart Citations
“…The intercalated anions are typical carbonates (CO 3 2À ), but can be simplys ubstituted by other anions( e.g.,N O 3À ,S O 4 2À ,C l À , Br À ). NiFe LDH, [65][66][67] NiMn LDH, [17,25] and NiCo LDH, [16,17] have been studied for OER, but main problem associated with Ni-based LDHs is their low conductivity (Ni 3 Fe LDH:1 .943 Scm; Ni 3 Fe LDHÀNH 3 :3 .759 Scm; Ni 3 Fe LDHÀAr:3 .061 Scm), which is ag eneral dilemma with hydroxides. NiFe LDH, [65][66][67] NiMn LDH, [17,25] and NiCo LDH, [16,17] have been studied for OER, but main problem associated with Ni-based LDHs is their low conductivity (Ni 3 Fe LDH:1 .943 Scm; Ni 3 Fe LDHÀNH 3 :3 .759 Scm; Ni 3 Fe LDHÀAr:3 .061 Scm), which is ag eneral dilemma with hydroxides.…”
Section: Ni-based Layered Double Hydroxide Nanosheet Oer Electrocatalmentioning
confidence: 99%
“…[17] Consequently,L DHs have gained attention for electrochemicalr eactions, they are capable of participating in anion exchange with the electrolyte. NiFe LDH, [65][66][67] NiMn LDH, [17,25] and NiCo LDH, [16,17] have been studied for OER, but main problem associated with Ni-based LDHs is their low conductivity (Ni 3 Fe LDH:1 .943 Scm; Ni 3 Fe LDHÀNH 3 :3 .759 Scm; Ni 3 Fe LDHÀAr:3 .061 Scm), which is ag eneral dilemma with hydroxides. [68] This obstacle can be resolved by either directly growing LDH on ac onductive substrate, such as carbon cloth, carbon nanotubes, carbon quantum dots, graphene, or Ni foam, or by hybridizing with ac onductive material.…”
Section: Ni-based Layered Double Hydroxide Nanosheet Oer Electrocatalmentioning
confidence: 99%
See 2 more Smart Citations
“…Layered double hydroxides can be prepared by different methods such as coprecipitation, hydrolysis with urea, sol-gel, hydrothermal treatment, combustion and mechanical synthesis, among others, with the most common and economic method being coprecipitation [23][24][25]. Studies have reported that the synthesis method, the conditions of synthesis, the type of cations and structural anions, the metal precursors and the metal ratio M 2+ /M 3+ are determining factors on the properties and applications of LDH [26][27][28][29]. An important element to improve the catalytic activity of LDH is the thermal treatment to form mixed spinel-type oxides, specifically in the production of biodiesel by heterogeneous catalysis [30,31].…”
Section: Introductionmentioning
confidence: 99%